1988
DOI: 10.1007/bf00377034
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the migratory behaviour of the toad Bufo bufo: direction and magnitude of movements

Abstract: The migratory behaviour of the toad Bufo bufo was studied from February 1985 to April 1986 in the submontane region of Bavaria, West Germany. Toads were fitted with a mechanical tracking device to record individual paths of migration. Three aspects of migratory behaviour were quantified: orientation in relation to the breeding site, straightness of path, and locomotory activity. The annual activity period began with migration from the hibernation sites to the breeding pond in April. The paths went straight tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
83
2
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(95 citation statements)
references
References 24 publications
9
83
2
1
Order By: Relevance
“…In turn, high amounts of precipitation permit spatial expansion which is reflected by an increase in occupancy (Cayuela et al 2012). Lower migration activity in relation to a low amount of precipitation in the breeding season was observed in several species (Sinsch 1988;Hartel 2008). Jakob et al (2003) found in a Mediterranean pond system that some species skipped the breeding season when unfavourable hydrological conditions occurred.…”
Section: Species Turnover and The Role Of Body Sizementioning
confidence: 99%
See 1 more Smart Citation
“…In turn, high amounts of precipitation permit spatial expansion which is reflected by an increase in occupancy (Cayuela et al 2012). Lower migration activity in relation to a low amount of precipitation in the breeding season was observed in several species (Sinsch 1988;Hartel 2008). Jakob et al (2003) found in a Mediterranean pond system that some species skipped the breeding season when unfavourable hydrological conditions occurred.…”
Section: Species Turnover and The Role Of Body Sizementioning
confidence: 99%
“…Gibbs 1998; Vos and Chardon 1998; Lehtinen et al 1999;Ficetola and De Bernardi 2004;Weyrauch and Grubb 2004;Curado et al 2011). While today the habitat preferences of most European amphibian species are relatively well known (Bell 1977;Sinsch 1988), our knowledge on the drivers of the assembly and dynamics of their communities is much more limited, especially at the landscape scale.…”
Section: Introductionmentioning
confidence: 99%
“…Site fidelity may give males a competitive advantage when females arrive to breed in the spring. Different energetic requirements associated with reproduction may require females to travel farther for foraging, and larger body sizes may allow females to do so (Turner, 1958;Sinsch, 1992;Bartelt et al, 2004). The reason movement patterns do not differ between sexes of R. kukunoris is unknown, but the lack of difference may be related to the lack of sexual size dimorphism in this species (Fei et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, with explicit knowledge of the composition and arrangement of preferred overwintering, breeding, and summer habitats of Wood Frogs (Lithobates sylvaticus), it was apparent that much less habitat area would require protection than perceived through traditional core habitat models (Baldwin et al, 2006). Sinsch (1990) suggested that habitats must provide four major resources for the annual activities of anurans: reproduction, nutrition acquisition, hibernation, and aestivation. In some circumstances, these resources may be located in the same habitat patch, and anurans need not consume energy resources to migrate (Pilliod et al, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation